Genomic analysis on Brazilian strains of Anaplasma marginale - Dall'Agnol, Bruno; Webster, Anelise; Souza, Ugo Araújo; Barbieri, Antonela; Mayer, Fabiana Quoos; Cardoso, Gisele Antoniazzi; Torres, Tatiana Teixeira; Machado, Rosangela Zacarias [UNESP]; Ferreira, Carlos Alexandre Sanchez; Reck, José (FapUNIFESP (SciELO), 2021)
Anaplasma marginale is a vector-borne pathogen that causes a disease known as anaplasmosis. No sequenced genomes of Brazilian strains are yet available. The aim of this work was to compare whole genomes of Brazilian strains of A. marginale (Palmeira and Jaboticabal) with genomes of strains from other regions (USA and Australia strains). Genome sequencing of Brazilian strains was performed by means of next-generation sequencing. Reads were mapped using the genome of the Florida strain of A. marginale as a reference sequence. Single nucleotide polymorphisms (SNPs) and insertions/deletions (INDELs) were identified. The data showed that two Brazilian strains grouped together in one particular clade, which grouped in a larger American group together with North American strains. Moreover, some important differences in surface proteins between the two Brazilian isolates can be discerned. These results shed light on the evolutionary history of A. marginale and provide the first genome information on South American isolates. Assessing the genome sequences of strains from different regions is essential for increasing knowledge of the pan-genome of this bacteria.